Fine structure of antennal sensilla of the spittlebug Philaenus spumarius L. (Insecta: Hemiptera: Aphrophoridae). I. Chemoreceptors and thermo-/hygroreceptors. Issue 5 (September 2016) - Ranieri, Emanuele; Ruschioni, Sara; Riolo, Paola; Isidoro, Nunzio; Romani, Roberto
Abstract: The meadow spittlebug, Philaenus spumarius (L.) (Hemiptera: Cercopoidea: Aphrophoridae), is a polyphagous species that transmits Xylella fastidiosa, a bacterium associated with "Olive Quick Decline Syndrome" in Southern Italy. In this study, the morphology and the ultrastructure of the antennal sensilla of P . spumarius were investigated. The antennae consist of three segments: a basal scape, a pedicel and a flagellum composed of a basal enlargement (ampulla) and a long segment (filament). The pedicel bears a single campaniform sensillum while the ampulla houses twelve coeloconic sensilla and three large basiconic sensilla. These latter sensilla show a smooth multiporous external cuticular wall and a total number of 27 sensory neurons per sensillum. The coeloconic sensilla belong to two morphologically distinct types: double-walled and single-walled sensilla. The sensory peg of the double-walled sensilla is smooth at the base and distally has a grooved cuticular surface with pores organized in spoke channels between each ridge. Three sensory neurons enter the lumen while at the basal level, before entering the peg, a fourth sensory neuron is found. The single-walled sensilla show an aporous thick cuticular wall and two sensory neurons entering the sensillar lumen, with a third neuron ending at the sensillum base. Graphical abstract: Highlights: Antennae of Philaenus spumarius were investigated by SEM and TEM. The map and the characterization of antennal sensilla is proposed. Flagellum shows three basiconi sensilla, twelve coeloconic sensilla and a scolopidium. The antenna of P. spumarius presents a strong reduction in olfactory sensilla.